KERJASAMA INDONESIA DAN SPANYOL DALAM MENANGANI AKSI TERORISME TAHUN 2015 - Ermanila Supandi; Fendy Eko Wahyudi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Indonesia establish a cooperation on terrorism with Spain in 2015. This cooperation is one of Indonesia's support for the terrorism campaign led by the US after the of September 11, 2001 events. Indonesia is one of the international actors who are also incorporated in the international system. Meaning that, Indonesian political behavior is also influenced by systems and international politics. It also conveys that in responding to the issue of terrorism globally, Indonesia should cooperate with another country, one being with Spain. However, the events of terrorism in Indonesia and Spain have no connection. This study aims to explain why Indonesia cooperates with Spain regarding terrorism. Qualitative research methods, with explanative types, are used in this study to discuss the factors that encourage Indonesia to collaborate with Spain. Meanwhile, the framework used in this research is Foreign Policy Analysis delivered by David Singer with the unit of analysis (dependent variable) of the country and explanation unit international system / global system.